Cu/GDC cermet anodes by sintering via surface modification with MgO sol - Han, Kyoung R.; Jeong, Younji; Kim, Chang-Sam; Lee, Haiwon (ECO-MATERIALS PROCESSING AND DESIGN VIII, 2007)
CuO/GDC composite powder with 50 wt% of CuO was prepared by surface modification of similar to 60 nm GDC powder with Cu precursors. Since copper oxide melts at lower temperature than GDC sintering temperature, fabrication procedure was modified by inducing infiltration of molten copper oxide via capillary force and then followed by heat treatment at similar to 1000 degrees C. Surface modification was carried out with a MgO sol to suppress agglomeration of GDC. Such prepared Cu/GDC cermets showed uniform microstructure and excellent electronic conductivity of similar to 8500 S/cm for the Cu/GDC cermet and similar to 10200 S/cm for the modified one at 800 degrees C.